Short-term Outcomes of Arthroscopic Treatment of Freiberg’s Disease - Kwang-Bok Lee MD, PhD; Do-Yeon Kim; Jong-Kil Kim (Foot & Ankle Orthopaedics)
Category: Arthroscopy; Midfoot/Forefoot Introduction/Purpose: Freiberg’s disease is also known as avascular necrosis (AVN) of the metatarsal head. Surgical treatment for Freiberg’s disease has not been completely defined yet. The purpose of this retrospective study was to evaluate short-term outcomes following arthroscopic procedures for treating Freiberg’s disease. Methods: From 2015 to 2019, 13 patients (15 feet) diagnosed with Freiberg’s disease were enrolled for arthroscopic surgery. Patients were divided based on the Smillie’s classification system (2 with stage I, 8 with stage II, 3 with stage III, 1 with stage IV, and 1 with stage V). Arthroscopic interventions, including synovectomy, debridement, chondroplasty, microfracture, and loose body removal, were performed for all patients without considering their Smillie's classification stages. Radiological outcomes were evaluated by X-rays (preoperatively and at 3, 6, and 12 months postoperatively) and MRIs (preoperatively and postoperative 12 months). Clinical outcomes were evaluated using the American Orthopedic Foot Ankle Society (AOFAS) lesser metatarsophalangeal (MTP)-interphalangeal score and the Visual Analogue Scale (VAS) score. The range of motion (ROM) of the MTP joint was measured using a goniometer both preoperatively and postoperatively. Results: Radiological study showed no evidence of osteonecrosis progression in post-operative 12 months X-ray images of any cases. Postoperative 12-month MRIs showed reduction of bone-marrow edema, irregularity of subchondral bone, and cartilage defects in all cases. Significant improvements of AOFAS scores and VAS scores occurred at all postoperative time points compared to preoperative scores (P = 0.001). MTP joint ROM also showed improvement at the last follow-up (P = 0.001). Conclusion: Arthroscopic surgery for Freiberg’s disease showed excellent clinical outcomes, MTP joint ROM, and short-term outcomes regardless of grades (Smillie’s classification system) in radiological evaluation.